Bryophyte literature records database of Aysén, Chilean sub-Antarctic ecoregion - Sánchez Jardón, Laura; Hernández de Diego, A.; Mackenzie, R.; Villodre Torrente, María; Schmitz García, María Fe; Acosta Gallo, Belén (Scientific Data, 2025)
The SIB-Aysén was developed with financing from the Regional Government of Aysén through the Competitiveness Innovation Fund (FIC) for the project “Biodiversity Information System for Aysén (BIP 30346481-0)”. The work is being continued with the support of the Cape Horn International Center (CHIC, ANID/BASAL FB210018). The Chilean sub-Antarctic ecoregion hosts the largest expanse of temperate forests, wetlands and peatlands, as well as the largest proportion of protected areas in the southern hemisphere. Bryophytes are highly diverse and ecologically essential in sub-Antarctic ecosystems and are considered as biodiversity loss indicators caused by the current socio-ecological crisis. However, knowledge about their biodiversity is rather limited. Integrating the available information on bryophyte diversity in regional platforms such as SIB-Aysén can be useful to acknowledge their ecological importance and remarkable biodiversity. This article integrates 345 records of 273 bryophyte taxa known in the region of Aysén and emphasizes the need to include citizen science as a tool to increase observations in lesser-known taxonomic groups. Gobierno Regional de Aysén Cape Horn International Center Depto. de Biodiversidad, Ecología y Evolución Fac. de Ciencias Biológicas TRUE pub